Blended Learning: Cara Pelatihan Masa Depan Organisasi Koperasi - Rosmayati, Siti; Maulana, Arman (Koaliansi : Cooperative Journal, 2023)
Blended learning is a new term for people working in the learning and development industry. In this format, it does not hinder face-to-face learning. With learning and training, employees can immediately take part in online training on the topics needed. It addresses the challenges of Cooperative companies with distributed or distributed workforces by combining the benefits of in-person and online learning. The biggest benefit is that employers do not need to invest anything or rely on special innovations to increase the effectiveness of employee training programs. It also offers unparalleled flexibility, enhances learning, is self-organizing, reduces travel costs, accelerates current communications and can overcome misunderstandings during virtually continuous training.